We need mutual aid too: group work instructors helping each other navigate online teaching. Issue 1 (2nd January 2023) - Bergart, Ann; Currin-McCulloch, Jennifer; Lind, Kristina; Chilwalo, Namoonga B.; Guy, Donna Louise; Hall, Neil; Kelly, Diana; Lee, Cheryl D.; Mesbur, Ellen Sue; Muskat, Barbara; Saldanha, Kennedy; Seck, Mamadou M.; et al.
ABSTRACT: The introduction of COVID-19 disrupted almost every facet of global societies, including institutions of higher education. With limited time to prepare for the emergent shift to virtual instruction, few educators had the time or emotional energy to invest in course redesign to meet established standards of quality online education. Strained by lack of guidance from their institutions and limited confidence in teaching social group work virtually, twelve group work educators initially participated in a weekly mutual aid group of peer members sponsored by the International Association for Social Work with Groups. This paper describes the evolution of a peer-facilitated, international, mutual aid group for group work educators making the transition to an online format – its conception, formation, purpose, structure, facilitation, and process. The authors address the personal experiences of all members, and place the group into a theoretical context.